Primary School Teachers’ Conceptions of Reading Comprehension Processes and Its Formulation - Zhu, Xinhua; Cheong, Choo Mui; Li, Guan Ying; Wu, Jacqueline (Frontiers in Psychology, 2020)
Understanding reading comprehension processes is vital for teachers to effectively conduct teaching and assessment of reading in schools. Hong Kong students’ outstanding reading performance internationally is commonly attributed to the implementation of reading comprehension models in its Chinese language curriculum; however, the understanding of teachers’ conceptions of reading comprehension is still very limited. This phenomenographic study interviewed twenty-nine in-service Chinese language teachers from eight Hong Kong primary schools and illustrated the elicited conceptions of a model of reading comprehension processes (i.e., Six Types of Reading Comprehension Process Model, a widely used model in Hong Kong). The three categories of teachers’ conceptions found are: understanding basic ideas of a text, sequential development of holistic comprehension skills, and fostering independent readers. This study further employed sense-making theory to investigate the formulation of the teachers’ conceptions. It is found that the conceptions were shaped when teachers’ conventional practices that focused on rote-learning interplayed with the continual regulating means of the implementation. Teachers are also highly influenced by factors like attainability by their students and agreement with own philosophy. This study also implied that teachers’ beliefs will need to be brought to light in order for new learning to happen.